ENDOFIT ACHITQILARNING BIOXILMA-XILLIGI VA IDENTIFIKATSIYASI - Shodieva, D.Gʻ.; Abdulmyanova, L.I.; Bahodirova, M.B. (SCIENCE and SOCIETY, 2025)
The article describes 50 endophytic yeasts isolated from the generative parts of 18 plants in our republic. In addition to characterizing the strains are considered isolated using classical methods, modern approaches to accurately classify yeasts at the species level, including molecular genetic methods,. As a result were identified, 6 genera and 9 species of endophytic yeasts. In addition, it was possible to identify the Starmerella bacillaris strain, previously known as Candida zemplinina.